Comparison of Early Versus Delayed Showering on Post-Operative Wound Infections - Salman Habib Abbasi; Abdul Basit; Muhammad Farooq; Fazal Hussain Shah (Journal of Bahria University Medical and Dental College)
Objectives: To compare frequency of SSIs with and without early showering after clean and clean contaminated surgical wounds. Study Design and Setting: Randomized controlled trial was conducted at Department of Surgery. HIT Hospital, Taxila from June 2020 to December 2020. Methodology: A total of 130 participants were recruited after taking informed consent. After clean and clean-contaminated surgery, first group was subjected to early showering (48 hours after surgery) while second group was not allowed showering until removal of stiches. Both groups were compared in terms of SSIs. Data was entered into SPSS version 25. The mean and standard deviation were used for the expression of continuous variables while frequency and proportion were used for qualitative variables. Both groups were compared by independent sample t test and chi square test. A p value of <0.05 was considered statistically significant. Results: The mean age of the patients was 39.92 ± 11.42 years and there was male gender dominancy i.e. 74 (56.9%) were males while 56 (43.1%) were females. Clean surgeries were 81 (62.3%) and clean-contaminated proportion was 49 (37.7%). Collectively, 12 (9.2%) patients developed SSIs during clinical followup. There was no difference between groups in terms of age, gender, and wound types (p values 0.680, 0.157 and 0.587 respectively). In shower group, 3 (4.6%) and in nonshower group, 9 (13.8%) patients developed SSIs (p value 0.069). Conclusion: Early postoperative showering can be implemented safely in clean and clean contaminated surgical wounds to minimize SSIs. The results should be evaluated in large RCTs.